Taking L3 learning by the horns: benefits of computer-mediated intervention for dyslexic school children. Issue 3 (1st September 2016) - Pfenninger, Simone E.
Abstract : This study investigates the interrelation of motivation, autonomy, metacognition, and L3 gains made as a function of three months of intervention with computer software specifically designed for the private use of dyslexic Swiss German learners of Standard German as a second language (L2) and English as a third language (L3). Based on questionnaire data and phonological/orthographic and semantic L3 measures gathered from 40 subjects (ten dyslexic participants receiving special training, ten normal readers matched on training situation, ten controls matched on reading ability, ten controls with median reading abilities), it was found that self-directed, multi-sensory training in the L3 is a potentially important tool in intervention for dyslexic students, as it not only allows the students to improve in learning foreign languages but also to move from feelings of apprehension and doubt to linguistic self-confidence. Thus, the results allow us to gain further insight into the L3 learning experiences of dyslexic elementary school students in a learner-directed learning environment, contributing to the existing body of research on the educational importance of learners developing autonomy and metacognition.